From Research Project to Research Portfolio: Meeting Scale and Complexity - Jonathan Linton; Nicholas Vonortas (Foresight and STI Governance, 2015)
The article considers how the past and present tendency to focus on selecting the best projects based on the sole criterion of meritorious science may result in a sub-optimal portfolio. The authors argue that scientists need to proactively engage in the discussion over the need to improve the efficiency and effectiveness of societal investments to ensure that the next generation of the management and decision-making process for our science, technology and innovation system is rooted in sound principles.The classic peer review process tends to provide unintended overlap and allows for an ill fit between some of the pieces and unwanted gaps to occur. Areas of high risk and high return can be missed due to their controversial nature and split decisions typically resulting in negative funding decisions. In general, high risk and a high frequency of split decisions tend to be replaced with lower risk initiatives. The authors propose herein supplementing peer review with research portfolio evaluation approaches and decision-making tools that can better assess research uncertainties and other special features of the transformation of the resulting knowledge into improved social well-being. A coupling of research quality review by peers with more systematic portfolio meta-analysis of recommended projects is both possible and essential.